Generalized erythroderma in a neonate: Rare presentation of nosocomial candidemia with Candida tropicalis - Dipak, Niraj Kumar; Sheikh, Samir Sultanbhai; Madhusudhan, D S; Kikani, Kishore Kanajibhai; Gandhi, Prachi; Shetty, Deepa (Indian Journal of Child Health, 2016)
Candida species are currently one of the most common causes of nosocomial infection in neonatal intensive care units with Candida tropicalis emerging as a frequent offending agent. Colonization precedes systemic invasive fungal infections in neonates. It generally manifests with lethargy, increased apneic episodes, feeding intolerance, late-onset thrombocytopenia, hypoglycemia, unexplained hyperglycemia, poor perfusion, and need for increased ventilator requirement. We report a 10-day-old neonate, with late-onset sepsis by C. tropicalis, presenting as generalized erythroderma. We present this case to highlight that nosocomial candidemia with C. tropicalis can present as generalized erythroderma in neonates. Maintaining adequate oral or parenteral fluid intake with monitoring of serum electrolytes is mandatory.